2020
DOI: 10.1080/22221751.2020.1846462
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in children across three Asian cosmopolitan regions

Abstract: As another wave of COVID-19 outbreak has approached in July 2020, a larger scale COVID-19 pediatric Asian cohort summarizing the clinical observations is warranted. Children confirmed with COVID-19 infection from the Republic of Korea, the Hong Kong Special Administrative Region (HKSAR) and Wuhan, China, during their first waves of local outbreaks were included. Their clinical characteristics and the temporal sequences of the first waves of local paediatric outbreaks were compared. Four hundred and twenty thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 27 publications
1
18
0
4
Order By: Relevance
“… 17 Multiple pediatric studies in Asia have reported that MIS-C is extremely rare, if not absent, among East Asian populations, despite Kawasaki disease being significantly more prevalent in Asia than in the rest of the world. 4 , 5 , 18 Multinational collaborative studies are needed to explain the genetic predisposition for MIS-C across different ethnicities. It is recommended that pediatricians in Asia treating children and youths who have COVID-19 and are not East Asian consider the development of MIS-C after the primary infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 17 Multiple pediatric studies in Asia have reported that MIS-C is extremely rare, if not absent, among East Asian populations, despite Kawasaki disease being significantly more prevalent in Asia than in the rest of the world. 4 , 5 , 18 Multinational collaborative studies are needed to explain the genetic predisposition for MIS-C across different ethnicities. It is recommended that pediatricians in Asia treating children and youths who have COVID-19 and are not East Asian consider the development of MIS-C after the primary infection.…”
Section: Discussionmentioning
confidence: 99%
“… 3 These public health policies have had a far greater impact than expected, and nearly all children and youths with COVID-19 in Hong Kong have had only mild illness. 4 , 5 During the 4 COVID-19 outbreaks, the Government of Hong Kong implemented territory-wide school closures intermittently. 6 , 7 During each school closure, face-to-face teaching was replaced by homeschooling and online classes.…”
Section: Introductionmentioning
confidence: 99%
“…Children with respiratory symptoms and headache were more likely to have higher saliva viral loads, but there were no significant differences in their NPS viral loads. Pediatric cross-sectional studies have shown that approximately 30% – 50% children did not present with fever [ 2 , 21 ], which suggested NPS viral load might not be the best to correlate with the clinical symptoms and immunological profiles. In a recent study by Chong et al with a smaller sample size of 18 children that compared cycle threshold values of SARS-CoV-2 in NPS and saliva, they concluded that saliva was not useful for the diagnosis of children with COVID-19 [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the coronavirus disease 2019 (COVID-19) outbreak in late December 2019, more than 81 million people have been infected globally and more than 1.8 million people have died [ 1 ]. Studies in Asia reported the majority of children with COVID-19 had only mild symptoms [ 2 , 3 ]. Children with COVID-19 had various symptoms including fever, pneumonia, and low lymphocyte count that were associated with prolonged viral shedding [ 4 ], whereas their immunoglobulin G (IgG) and neutrophil to lymphocyte ratio were negatively associated with liver and myocardial enzymes [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In general, children have a shorter and milder disease than adults [ 239 , 240 ]. However, a rare but life-threatening Kawasaki-like disease, known as multisystem inflammatory syndrome in children (MIS-C) or paediatric inflammatory syndrome temporally associated with SARS-CoV-2, are seen during the convalescent phase of the illness [ 97 , 241 ].…”
Section: Clinical Manifestationsmentioning
confidence: 99%